Paths to the Professoriate : Strategies for Enriching the Preparation of Future Faculty - Wulff, Donald H. and Austin, Ann E. (San Francisco Jossey-Bass, 2004)
Because fifty percent of the current higher education faculty will retire over the next ten years, the topic of how to prepare the next generation of faculty members is vital to administrators, faculty developers, and researchers across the field of higher education. This book is a much-needed resource that is a collection of the work from key researchers in the field who report on the most compelling work currently being done.
Include Index
Keywords: Universities and colleges--Faculty -- United States